PENGARUH SELF-EFFICACY, PERTIMBANGAN PASAR KERJA, DAN PENGETAHUAN PERPAJAKAN TERHADAP MINAT BERKARIR MAHASISWA SEBAGAI KONSULTAN PAJAK - Rizky Nirmalasari; Andy Dwi Bayu Bawono (JURNAL LENTERA BISNIS, 2025)
The purpose of this study is to analyze the effect of self-efficacy, labor market considerations, and taxation knowledge on students' career interest as tax consultants. This type of research is quantitative research. In this study, the method used for sampling was non-probability with purposive sampling technique. The type of data used is primary data. The data collection technique used in this research is a questionnaire. The data analysis techniques used are descriptive statistical tests, validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, hypothesis tests, multiple linear regression tests, coefficient of determination tests, F tests, and T tests. The results of this study are self-efficacy has a positive and significant effect on students' career interest as tax consultants. Labor market considerations have a positive and very significant effect on students' career interest as tax consultants. Tax knowledge has a positive but insignificant effect on students' career interest as tax consultants.